ADE610 - Interactive Multimedia / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
This course provides to the students in learning the principles and fundamental techniques, skills and processes of creating interactive multimedia through hands-on activities. It involves in critically reviewing current visual art professional multimedia projects as an important part of the learning process. Macromedia Director or other relevant software will be used to integrate all the media and imported animations. Specific software instruction will introduce the students to text & graphics, digital-imaging processes and manipulation, sound and video digitizing and the use of existing pre-created animations. Students are free to use and explore any other software available in the computer laboratory. The final emphasis is on designing a creative and functional multimedia interface.